Cardio-oncology: Understanding the different mechanisms of cardiovascular toxicity - Júlia Cristina Toste (Revista Portuguesa de Cardiologia, 2022)
Due to the success of finding treatments for various types of cancer, overall cancer survival has increased substantially in recent decades. Ironically, the clinical success of antineoplastic therapy is attenuated by the comorbidity of cardiovascular diseases, which appear to be the main complications of intense cancer treatment and are the second main cause of long-term morbidity and mortality among cancer survivors.Cardio-oncology is the new area of cardiology that aims to treat the specific cardiologic status of cancer patients.Most antineoplastic therapies are associated with some degree of cardiovascular toxicity, ranging from asymptomatic and transient cardiac events to clinically significant and long-lasting events.Antineoplastic agents are responsible for different cardiovascular injuries, which can be reversible or permanent. All anatomical structures of the heart can, however, be affected by transthoracic radiotherapy.Cardiotoxicity mechanisms are recognized according to the presence or absence of structural anomalies and their reversibility, being classified into Type I and Type II, aiming to distinguish the drugs that induce irreversible damage (Type I) from the drugs that predominantly induce reversible left ventricular dysfunction (Type II).While anthracyclines and anti-HER2 agents form the two major groups of cardiotoxic drugs, other antineoplastic agents, such as other monoclonal antibodies, certain tyrosine kinase inhibitors and antiangiogenic drugs can also be cardiotoxic via different mechanisms.This article presents the different pathophysiological mechanisms of cardiovascular toxicity according to the treatment regimen used. Resumo: Devido ao sucesso obtido em encontrar tratamentos para vários tipos de cancro, a taxa de sobrevida global do cancro aumentou substancialmente nas últimas décadas. Ironicamente, o sucesso clínico da terapêutica antineoplásica é atenuado pela comorbilidade das doenças cardiovasculares, que surgem como as principais complicações do tratamento oncológico intenso e constituem a segunda principal causa de morbilidade e mortalidade a longo prazo entre os sobreviventes de cancro.A cardio-oncologia é a nova área da cardiologia que visa tratar as situações cardiológicas dos doentes oncológicos com toda a sua especificidade.A maioria das terapêuticas antineoplásicas está associada a algum grau de toxicidade cardiovascular, variando desde eventos cardíacos assintomáticos e/ou transitórios a eventos clinicamente significativos e de longa duração.Os agentes antineoplásicos são responsáveis por diferentes lesões cardiovasculares, que podem ser reversíveis ou permanentes. Por outro lado, todas as estruturas anatómicas do coração podem ser afetadas pela radioterapia transtorácica.Os mecanismos de cardiotoxicidade são reconhecidos, de acordo com a presença ou não de anomalias estruturais e sua reversibilidade, classificando-se em Tipo I e Tipo II, procurando distinguir os fármacos que induzem danos irreversíveis (Tipo I) dos fármacos que induzem predominantemente disfunção ventricular esquerda reversível (Tipo II).Enquanto antraciclinas e agentes anti-HER2 formam os dois grandes grupos de fármacos cardiotóxicos, outros agentes antineoplásicos, como outros anticorpos monoclonais, certos inibidores de tirosina-kinase e fármacos antiangiogénicos, também podem ser cardiotóxicos através de diferentes mecanismos.Neste artigo apresentam-se os diferentes mecanismos fisiopatológicos de toxicidade cardiovascular de acordo com o esquema de tratamento usado.